Prototype Alat Pendeteksi & Pengukur Kebocoran Gas Berbasis IoT - Lontaan, Rolly Junius (TeIKa, 2025)
The widespread use of LPG gas in households and industries poses a leakage risk that can potentially cause fires. This study aims to develop a prototype of an IoT-based gas leakage detection and measurement device, enabling remote monitoring via the Telegram application. The research methodology includes needs analysis, hardware and software design, system implementation, testing, and evaluation. The results indicate that the developed system, utilizing the MQ2 sensor and NodeMCU, can accurately detect gas leaks and send real-time notifications to users. This system provides an effective early warning, enhances user safety, and overcomes the limitations of the human sense of smell in detecting gas leaks.